Pengaruh Pengawasan Internal dan Kepemimpinan Terhadap Kinerja Karyawan (Studi Kasus di Politeknik LP3I Jakarta) - Rita Wahyuni (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
This study aims to analyze how much influence internal control, leadership to employee performance level. Sampling method used is Proportionate Random Sampling. The sample in this study followed the formula Slovin, or as many as 70 employees Polytechnic LP3I Jakarta. The data that have fulfilled the validity and reliability test are then processed to produce the regression equation Y = -12.882 + 0.852 X1 + 0.352 X2, where Y is the employee performance variable, X1 is the internal control variable and X2 is the leadership variable.The result of the research also shows that internal control influence to employee performance, leadership influence to employee performance, internal control and leadership have influence to employee performance. The relationship of internal supervision and leadership to employee performance is very strong and internal captive variables and leadership can explain employee's performance of 72.9%, while the rest of 27,1% is explained by other variables.